Prevalence and consequences of mineral and vitamin deficiencies and interventions to reduce them - Boy, Erick (International Food Policy Research Institute, 2014)
Few data exist on the aetiology of anaemia and Fe deficiency (ID) during early infancy in South Asia. The present study aimed to determine the contribution of ID, infections and feeding practices to anaemia in Bangladeshi infants aged 6–11 months. Baseline data from 1600 infants recruited into a cluster-randomised trial testing the effectiveness of micronutrient powder sales by frontline health workers on the prevalence of anaemia were used. Multivariate logistic regression was used to identify risk factors for anaemia and ID, and population attributable fractions (PAF) were computed to estimate the proportion of anaemia that might be prevented by the elimination of individual risk factors. It was found that 68 % of the infants were anaemic, 56 % were Fe deficient, and one-third had evidence of subclinical infections. The prevalence of anaemia and ID increased rapidly, until 8–9 months of age, while that of subclinical infections was constant. ID (adjusted OR (AOR) 2·6–5·0;P< 0·001) and subclinical infections (AOR 1·4–1·5;P< 0·01) were major risk factors for anaemia, in addition to age and male sex. Similarly, subclinical infections, age and male sex were significant risk factors for ID. Previous-day consumption of Fe-rich foods was very low and not associated with anaemia or ID. The PAF of anaemia attributable to ID was 67 % (95 % CI 62, 71) and that of subclinical infections was 16 % (95 % CI 11, 20). These results suggest that a multipronged strategy that combines improvements in dietary Fe intake alongside infection control strategies is needed to prevent anaemia during infancy in Bangladesh.